Die keusche Penelope und der zornige Odysseus : Kursieren einer tragikomischen Opernhandlung zwischen Wien und Norditalien - Livio Marcaletti (Musicologica Brunensia, 2018)
In the 1710s and 1720s, librettist Pietro Pariati and composer Francesco Bartolomeo Conti cultivated the highly specific genre of tragicommedia per musica at the Habsburg court in Vienna. Of particular interest is their tragicomedy Penelope (1724), which depicts Ulysses as a ridiculous hero guided by his furious jealousy through a comedy of errors where mistaken identity and buffo servants play a relevant role. Far from being new, this tragicomic interpretation of Ulysses's return to Ithaca belonged to a long-running tradition: Nicolò Minato's Penelope (Vienna 1670) inspired Matteo Noris's Penelope la casta (Venice 1685), on which Pariati in turn based his spoken tragicomedy La casta Penelope (Milan 1707) and the 1724 Viennese tragicommedia per musica. The present paper focuses on the dramaturgical evolution of this plot and shows a case study of bidirectional librettistic influence along the Vienna-Venice axis.